Prevailing in the digital age: resilient records to avoid drowning in a sea of data - Fernández Cuesta, Francisco; Hernández Olivera, Luis (Tábula, 2021)
What are the consequences of the shift towards data for our profession? What is the future role of archives and their professionals in this data age? The reflection on these issues was the central axis of the eighth Castile-Leon Conference on Archives that, between April 14 and 16, brought together more than two hundred professionals of information, documentation and archives, and an unbeatable speaking staff. A conference that, for the first time, had to be held entirely online, circumstance that did not devalue at all the quality of the contents that were addressed in it and that to a large extent are reproduced in this issue of Tábula .